Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Our platform connects you with professionals ready to provide precise answers to all your questions in various areas of expertise. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
1)
3x-2y=14
y=5x
So we plug in y=5x into 3x-2y=14
We get:
3x-2(5x)=14
3x -10x=14
-7x=14
x=-2
So we found x, now we need to find y. We can simply plug in x into the equation and get y.
y=5x
y=5(-2)
y=-10
So your answer will be (-2,-10).
2)
x-2y= -2
y= 2x+4
Once again plug in y=2x+4 into x-2y=-2
x-2(2x+4) = -2
x-4x-8=-2
-3x-8=-2
-3x = 6
x= -2
Now we plug back in x and solve for y :)
y=2x+4
y=2(-2)+4
y=-4+4
y=0
So our solution would be (-2,0).
3)
x+2y=-7
x-5y=7
Multiply the second equation by -1
-x+5y=-7
Now add that equation with the other one:
x+2y=-7
+
-x+5y=-7
-----------------
7y=-14
y=-2
Now plug in y=-2 and solve for x
x+2y=-7
x+2(-2)=-7
x+(-4)=-7
x-4=-7
x=-3
So your solution would be (-3,-2).
3x-2y=14
y=5x
So we plug in y=5x into 3x-2y=14
We get:
3x-2(5x)=14
3x -10x=14
-7x=14
x=-2
So we found x, now we need to find y. We can simply plug in x into the equation and get y.
y=5x
y=5(-2)
y=-10
So your answer will be (-2,-10).
2)
x-2y= -2
y= 2x+4
Once again plug in y=2x+4 into x-2y=-2
x-2(2x+4) = -2
x-4x-8=-2
-3x-8=-2
-3x = 6
x= -2
Now we plug back in x and solve for y :)
y=2x+4
y=2(-2)+4
y=-4+4
y=0
So our solution would be (-2,0).
3)
x+2y=-7
x-5y=7
Multiply the second equation by -1
-x+5y=-7
Now add that equation with the other one:
x+2y=-7
+
-x+5y=-7
-----------------
7y=-14
y=-2
Now plug in y=-2 and solve for x
x+2y=-7
x+2(-2)=-7
x+(-4)=-7
x-4=-7
x=-3
So your solution would be (-3,-2).
1)
[tex]3x-2y=14\\ \\ y=5x[/tex]
We know y's value. Let's plug it in the equation.
[tex]y=5x\\ \\ 3x-2\cdot (5x)=14\\ \\ 3x-10x=14\\ \\ -7x=14[/tex]
Divide both sides by -7.
[tex]x=-2[/tex]
Now we have x's value. Let's plug it in the equation to find y.
[tex]x=-2\\ \\ y=5x\\ \\ y=5\cdot -2\\ \\ y=-10[/tex]
Solution,
(-2, -10)
2)
[tex]x-2y=-2\\ \\ y=2x+4[/tex]
Again we have y's value. Let's plug and solve.
[tex]y=2x+4\\ \\ x-2\cdot (2x+4)=-2\\ \\ x-(2\cdot 2x+2\cdot 4)=-2\\ \\ x-4x-8=-2\\ \\ -3x-8=-2\\ \\ -3x=-2+8\\ \\ -3x=6\\ \\ x=\frac { 6 }{ -3 } \\ \\ x=-2[/tex]
Now we have x's value let's solve for y.
[tex]x=-2\\ \\ y=2x+4\\ \\ y=2\cdot (-2)+4\\ \\ y=-4+4\\ \\ y=0[/tex]
Solution,
(-2, 0)
3)
[tex]x+2y=-7\\ \\ x-5y=7[/tex]
Let's first multiply the first equation by -1
[tex]-1\cdot (x+2y)=-1\cdot -7\\ \\ -x-2y=7[/tex]
Then let's add these new equation and the second equation.
[tex]-1\cdot (x+2y)=-1\cdot -7\\ \\ -x-2y=7\\ \\ x-5y=7\\ \\ (-x-2y)+(x-5y)=7+7\\ \\ -x+x-2y-5y=14\\ \\ -7y=14\\ \\ y=\frac { 14 }{ -7 } \\ \\ y=-2[/tex]
Now we have y's value let's plug it and solve for x.
[tex]y=-2\\ \\ x+2y=-7\\ \\ x+2\cdot (-2)=-7\\ \\ x-4=-7\\ \\ x=-7+4\\ \\ x=-3[/tex]
Solution,
(-3, -2)
[tex]3x-2y=14\\ \\ y=5x[/tex]
We know y's value. Let's plug it in the equation.
[tex]y=5x\\ \\ 3x-2\cdot (5x)=14\\ \\ 3x-10x=14\\ \\ -7x=14[/tex]
Divide both sides by -7.
[tex]x=-2[/tex]
Now we have x's value. Let's plug it in the equation to find y.
[tex]x=-2\\ \\ y=5x\\ \\ y=5\cdot -2\\ \\ y=-10[/tex]
Solution,
(-2, -10)
2)
[tex]x-2y=-2\\ \\ y=2x+4[/tex]
Again we have y's value. Let's plug and solve.
[tex]y=2x+4\\ \\ x-2\cdot (2x+4)=-2\\ \\ x-(2\cdot 2x+2\cdot 4)=-2\\ \\ x-4x-8=-2\\ \\ -3x-8=-2\\ \\ -3x=-2+8\\ \\ -3x=6\\ \\ x=\frac { 6 }{ -3 } \\ \\ x=-2[/tex]
Now we have x's value let's solve for y.
[tex]x=-2\\ \\ y=2x+4\\ \\ y=2\cdot (-2)+4\\ \\ y=-4+4\\ \\ y=0[/tex]
Solution,
(-2, 0)
3)
[tex]x+2y=-7\\ \\ x-5y=7[/tex]
Let's first multiply the first equation by -1
[tex]-1\cdot (x+2y)=-1\cdot -7\\ \\ -x-2y=7[/tex]
Then let's add these new equation and the second equation.
[tex]-1\cdot (x+2y)=-1\cdot -7\\ \\ -x-2y=7\\ \\ x-5y=7\\ \\ (-x-2y)+(x-5y)=7+7\\ \\ -x+x-2y-5y=14\\ \\ -7y=14\\ \\ y=\frac { 14 }{ -7 } \\ \\ y=-2[/tex]
Now we have y's value let's plug it and solve for x.
[tex]y=-2\\ \\ x+2y=-7\\ \\ x+2\cdot (-2)=-7\\ \\ x-4=-7\\ \\ x=-7+4\\ \\ x=-3[/tex]
Solution,
(-3, -2)
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.